UPAYA PENINGKATAN KUALITAS PENDIDIKAN MELALUI PERAN KKN TEMATIK POSDAYA BERBASIS MASJID - Rima Trianingsih; Sudarsri Lestari (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2018)
The implementation of this devotion program is based on a preliminary study indicated that the level of public education and awareness of the importance of education is still low. KKN Thematic Posdaya Mosque-Based Nurul Huda Rejoagung village Sumberagung sub-district Pesanggaran developed several programmes aimed at improving the quality of dedication to public education. The program runs well, among them tutoring, mentoring and training for the students of SMK Nusa Pesanggaran, and teaching TPQ. The program will be continued by the community in self-help.